Determinants of the primary stability of cementless acetabular cup implants: A 3D finite element study. (August 2021) - Immel, Katharina; Nguyen, Vu-Hieu; Dubory, Arnaud; Flouzat–Lachaniette, Charles-Henri; Sauer, Roger A.; Haïat, Guillaume
Abstract: Primary stability of cementless implants is crucial for the surgical success and long–term stability. However, primary stability is difficult to quantify in vivo and the biomechanical phenomena occurring during the press–fit insertion of an acetabular cup (AC) implant are still poorly understood. The aim of this study is to investigate the influence of the cortical and trabecular bone Young's moduli E c and E t, the interference fit IF and the sliding friction coefficient of the bone–implant interface μ on the primary stability of an AC implant. For each parameter combination, the insertion of the AC implant into the hip cavity and consequent pull–out are simulated with a 3D finite element model of a human hemi–pelvis. The primary stability is assessed by determining the polar gap and the maximum pull–out force. The polar gap increases along with all considered parameters. The pull–out force shows a continuous increase with E c and E t and a non-linear variation as a function of μ and IF is obtained. For μ  > 0.6 and IF  > 1.4 mm the primary stability decreases, and a combination of smaller μ and IF lead to a better fixation. Based on the patient's bone stiffness, optimal combinations of μ and IF can be identified. The results are in good qualitative agreement with previous studies and provide a better understanding of the determinants of the AC implant primary stability. They suggest a guideline for the optimal choice of implant surface roughness and IF based on the patient's bone quality. Highlights: Polar gaps increase as a function of bone stiffness, interference fit, and friction. Pull–out force increases continuously with increasing bone stiffness. Pull–out force peaks for interference fit of 1.4 mm and friction coefficient of 0.6 Optimal combinations of interference fit and friction maximize primary stability.